Ecoliteracy learning for classrooms and communities - Griswold, Wendy (Kansas State University, 2011)
The poster will provide a description of the use of book clubs in classroom and community settings to promote ecoliteracy. It will reference research literature on the topic as well aspractice based tips, reading lists and resources for further learning.
Keywords: Ecoliteracy; Book clubs; Reading lists